Convergence, Digitisation and New Technologies: Towards the Next Generation Network - Hanrahan, Hu (LINK Centre, University of the Witwatersrand (Wits), Johannesburg, 2001)
This paper introduces the concept of the Next Generation Network as the vision for convergence between the modern digital Public Switched Telecommunications Network and Internet Protocol Networks. The technological features of the NGN, as well as the business models that it facilitates, are described. Gateways to the PSTN are described. Migration of the PSTN to the NGN and further evolution of the NGN are outlined. The role of the NGN in providing universal service and universal access is outlined. An example of the use of NGN technologies to create next generation Telecentres is presented.